Tradisi Sende Sawah Pada Masyarakat Muslim Di Desa Sidomukti Kecamatan Weleri Kabupaten Kendal Indonesia Dalam Perspektif Maslahah - Rosyid, Irham Abdul; Fateh, Mohammad (el hisbah Journal of Islamic Economic Law, 2025)
The sende tradition is a local custom in Sidomukti Village, practiced as a form of mutual assistance among the predominantly farming community. In this tradition, rice fields are pledged to individuals with surplus funds in exchange for loans, with the land to be reclaimed upon repayment. This study aims to examine the compatibility of the contractual structure in the sende tradition with Islamic legal principles, ensuring its legitimacy and sustainability under Sharia law. This research employs an empirical legal method with a qualitative approach. Primary data were collected through observation, in-depth interviews, and document analysis, while secondary data were sourced from books, journals, and relevant literature. Data analysis followed Miles and Huberman’s qualitative model: data collection, reduction, display, and conclusion drawing. Findings indicate that the sende practice aligns more closely with the rahn (pledge) contract than with bai’ al-wafa (conditional sale). Despite its cultural entrenchment, implementation varies and community understanding of Islamic contracts remains limited. The transfer of land management rights, coupled with an agreement for future repossession, is generally accepted. However, to avoid riba (usury), the practice must be based on a clear, mutually agreed contract in line with Islamic principles.